Economic System and its Change: Methodological Problems - Lydeka, Zigmas (Ekonomika, 1998)
The article analyses the main indications of the economic system: elements, their relations, composition and behaviour. After having analyzed the terms of the economic system that are discussed in the scientific literature, the author has formulated such a description of the mentioned term: the economic system is an integrationed whole of the motivated economy subjects connected by various relations and acting according to the changeable environment. In the article there is presented the understanding of the economic system and its cycle in which the motion states of the economic system are distinguished: the start, the functioning and the ruin. The author differentiates among the development, the growth and the transformation terms, at the same time pointing out their relations with each other. The article also deals with the evolutional conceptions of the economic system, i.e. the functional, the structional and the marxist ones.